Vanished in the crowd - Bowen, Rhys; Broyles, Clare (Bowen, Rhys. Molly Murphy mysteries, 2026)
"Retired detective Molly Murphy Sullivan investigates the disappearance of a female scientist. New York is busier than ever as two million visitors come to the city to witness the Hudson-Fulton celebration in 1909, marking the 300th anniversary of Henry Hudson's discovery of the Hudson River. Parades, exhibitions, carnivals, and a marvelous display of the wonders of the latest invention -- electricity -- across the city make for two straight weeks of celebrations, which Molly and her family, along with their friends Sid and Gus, are excited to enjoy. But Molly is secretly dealing with financial troubles. She is too proud to ask her friends for a loan, but when they want to hire her as a detective she jumps at the chance. Sid and Gus are hosting fellow Vassar graduates to take part in one of the parades but one of the women, a brilliant scientist, never shows up. It seems nobody knows where she is, including her husband. Is she trying to run away from her life or is it something more sinister? Why have the Vassar women really come to New York City? When Daniel asks Molly to spy on her friends and find out just what they are planning, she finds her loyalties horribly divided. Then the parade turns deadly and only Molly has the tools to find out the truth" -- Provided by publisher.